Optical In-Process Measurement Systems - Fischer, Andreas (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Information is key, which means that measurements are key. For this reason, this book provides unique insight into state-of-the-art research works regarding optical measurement systems. Optical systems are fast and precise, and the ongoing challenge is to enable optical principles for in-process measurements. Presented within this book is a selection of promising optical measurement approaches for real-world applications.